Silicon-carbon composite material and method for manufacturing the same
Patent Information
- Application Number
- CN202311057997.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-08-22
AI Technical Summary
The existing technology for preparing silicon-carbon composite materials has low preparation efficiency, and there is a problem with the low preparation efficiency in the existing technology.
A novel preparation method is employed, in which a carbon source solution is flowed at high speed in a reaction chamber, and a low-pressure zone is generated near the efficient fluid. Silicon powder is adsorbed and enters the low-pressure zone. The air expansion between the silicon powder particles disperses the silicon particles and is adsorbed into the high-speed flowing carbon source solution, forming a silicon-carbon composite material with silicon particles as the core and a carbon layer as the shell.
It improves the specific capacity and cycle stability of silicon-carbon composite materials, solves the problem of low preparation efficiency in existing technologies, and is suitable for industrial production.
Smart Images

Figure BDA0004406621670000101
Abstract
Description
Technical Field
[0001] This invention relates to the field of negative electrode materials technology, and in particular to a silicon-carbon composite material and its preparation method. Background Technology
[0002] Among existing rechargeable battery systems, lithium-ion batteries are currently the most competitive in terms of both development potential and technical indicators such as lifespan, specific energy, operating voltage, and self-discharge rate. With the continuous development of electronic technology, higher demands are being placed on lithium-ion batteries, requiring higher energy density, better cycle life, better high and low temperature charge / discharge performance, and improved safety performance. This necessitates further development and improvement of the positive and negative electrode materials used in lithium-ion batteries.
[0003] Currently, carbon materials, such as natural graphite and graphitized mesophase carbon microspheres, are the most widely used anode materials for lithium-ion batteries. Among non-carbon anode materials, silicon possesses extremely high theoretical specific capacity, a low lithium storage reaction voltage plateau, and is widely distributed in nature, second only to oxygen in abundance in the Earth's crust. Therefore, silicon-based anode materials are a promising new type of high-energy material. However, the main problems with existing silicon-based anode materials are large volume changes during charge and discharge (up to approximately three times the original volume), poor conductivity, and instability of the solid-electrolyte interface film (SEI film). The industry mainly improves the performance of silicon-based anode materials through techniques such as nano-sizing, carbon coating, loading onto highly conductive carriers, pore formation, and pre-lithiation.
[0004] Current research on silicon-based anode materials mainly involves ball milling silicon powder with carbon source materials followed by pyrolysis to prepare silicon-carbon composite materials. This aims to alleviate volume expansion during battery charging and discharging and improve the cycle performance of silicon-based materials. However, ball milling requires a long time, and the mass produced per milling cycle is limited, resulting in low preparation efficiency. Summary of the Invention
[0005] The primary objective of this invention is to overcome the shortcomings of the prior art and provide a method for preparing silicon-carbon composite materials, thereby solving the technical problem of low preparation efficiency of existing silicon-carbon composite materials.
[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0007] A method for preparing a silicon-carbon composite material includes the following preparation steps:
[0008] Step 1: The carbon source solution is transported to the reaction chamber. The carbon source solution flows at high speed in the reaction chamber. A low-pressure zone is formed around the high-speed flowing carbon source solution. Silicon powder is introduced into the low-pressure zone. The air between the silicon powder particles expands in the low-pressure zone, causing the silicon particles to be dispersed. The silicon powder is also drawn into the high-speed flowing carbon source solution and discharged into the storage zone.
[0009] Step 2: The mixed solution in the storage area is dried, carbonized, pulverized, and sieved to obtain a silicon-carbon composite material.
[0010] The carbon source solution includes carbon nanotubes, polymers, and solvents.
[0011] The mass ratio of the carbon nanotubes, polymer, and solvent is 10-15:5-8:77-85.
[0012] The polymer is at least one of polyvinylpyrrolidone, polyacrylic acid polymers, polyether polymers, and polyurethane polymers.
[0013] The flow velocity of the carbon source solution in the reaction chamber is 10 m / s-20 m / s.
[0014] The air pressure in the low-pressure zone is -0.01MPa to -0.06MPa.
[0015] The gas pressure in the liquid storage area is not less than one atmosphere.
[0016] The silicon powder is nano-silicon or cracked silicon.
[0017] The method for preparing cracked silicon is as follows: immerse untreated silicon in an alkaline solution with a mass percentage concentration of 1-5%, react at 80-85℃ for 20-30 minutes, then wash with water until neutral and dry to obtain cracked silicon.
[0018] A second objective of this invention is to provide a silicon-carbon composite material, which is prepared by the above-described preparation method.
[0019] The beneficial effects of this invention are:
[0020] This invention utilizes the principle of low pressure and adsorption near a high-speed flowing fluid. First, a carbon source solution is transported to the reaction chamber and allowed to flow at high speed, creating a low-pressure zone around it. Then, silicon powder is introduced into the reaction chamber. The silicon powder is adsorbed and enters the low-pressure zone. Because the introduced silicon powder contains air, the air expands in the low-pressure zone, causing the silicon particles to disperse and be adsorbed into the high-speed flowing carbon source solution. This allows the silicon particles to be uniformly mixed with the carbon source solution. The silicon particles are wetted and encapsulated in the carbon source solution. After the mixed solution is discharged into the storage area, it is dried and carbonized, causing the carbon source to form a carbon layer on the surface of the silicon particles and encapsulate the silicon particles. This forms a silicon-carbon composite material with silicon particles as the core and a carbon layer as the shell, which can improve the specific capacity, cycle stability, and cycle life of the battery negative electrode.
[0021] The preparation method of the present invention does not require grinding and mixing of silicon powder and carbon source solution. Silicon-carbon composite materials can be continuously produced by continuously conveying carbon source solution and silicon powder, which is suitable for industrialization and can effectively improve production efficiency. Detailed Implementation
[0022] To make the objectives, technical solutions, and technical effects of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. The embodiments described below are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art in conjunction with the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed; where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0023] In the description of this invention, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0024] In the description of this invention, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0025] It should be understood that the weights of the relevant components mentioned in the embodiments of this invention can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this invention is within the scope of this invention. Specifically, the weights mentioned in the embodiments of this invention can be well-known units of mass in the chemical industry, such as μg, mg, g, and kg.
[0026] Furthermore, unless the context explicitly uses it otherwise, the singular form of a word should be understood as including the plural form of that word. The terms "comprising" or "having" are intended to specify the presence of a feature, quantity, step, operation, element, part, or combination thereof, but are not intended to exclude the presence or possible addition of one or more other features, quantities, steps, operations, elements, parts, or combinations thereof.
[0027] This invention provides a method for preparing a silicon-carbon composite material, which includes the following preparation steps:
[0028] Step 1: The carbon source solution is transported to the reaction chamber. The carbon source solution flows at high speed in the reaction chamber. A low-pressure zone is formed around the high-speed flowing carbon source solution. Silicon powder is introduced into the low-pressure zone. The air between the silicon powder particles expands in the low-pressure zone, causing the silicon particles to be dispersed. The silicon powder is also drawn into the high-speed flowing carbon source solution and discharged into the storage zone.
[0029] Step 2: The mixed solution in the storage area is dried, carbonized, pulverized, and sieved to obtain a silicon-carbon composite material.
[0030] This invention utilizes the principle of low pressure and adsorption near a high-speed flowing fluid. First, a carbon source solution is transported to the reaction chamber and allowed to flow at high speed, creating a low-pressure zone around it. Then, silicon powder is introduced into the reaction chamber. The silicon powder is adsorbed and enters the low-pressure zone. Because the introduced silicon powder contains air, the air expands in the low-pressure zone, causing the silicon particles to disperse and be adsorbed into the high-speed flowing carbon source solution. The silicon particles can then be uniformly mixed with the carbon source solution, becoming wetted and encapsulated by it. After the mixed solution is discharged into the storage area, it is dried and carbonized, causing the carbon source to form a carbon layer on the surface of the silicon particles, thus encapsulating the silicon particles. This forms a silicon-carbon composite material with silicon particles as the core and a carbon layer as the shell, which can improve the specific capacity, cycle stability, and cycle life of the battery negative electrode.
[0031] The preparation method of the present invention does not require grinding and dispersing of silicon powder and carbon source solution. Silicon-carbon composite materials can be continuously produced by continuously conveying carbon source solution and silicon powder, which is suitable for industrialization and can effectively improve production efficiency.
[0032] In this process, the mass ratio of the carbon source solution to silicon powder is 8-9:1. Using this range, the carbon layer of the resulting silicon-carbon composite material can continuously and completely encapsulate the silicon particles, preventing significant expansion of the silicon particles during charging and discharging. Furthermore, the anode material made from this silicon-carbon composite material has higher specific capacity and better conductivity, which is beneficial for improving battery charge / discharge rates, reducing energy loss, and enhancing battery cycle life. When the mass of the carbon source solution is too low, the carbon layer formed after carbonization cannot completely encapsulate the silicon particles. When the resulting silicon-carbon composite material is used in the anode material, it is prone to large volume expansion and mechanical stress, reducing the material's stability. Conversely, when the mass of the carbon source solution is too high, the silicon content is low, which reduces the specific capacity of the anode material.
[0033] The carbon source solution comprises carbon nanotubes, a polymer, and a solvent. The carbon source solution is prepared by mixing carbon nanotubes and the polymer with the solvent. After carbonization, a carbon layer is formed on the surface of silicon particles, where carbon nanotubes and porous amorphous carbon are cross-linked. The carbon nanotubes are interspersed within the porous amorphous carbon layer, encapsulating the silicon particles and forming a reinforced concrete-like structure on the surface of the silicon particles. This improves the overall structural stability of the silicon-carbon composite material. Furthermore, the excellent conductivity of carbon nanotubes enhances the conductivity of the silicon-carbon composite material, while the porous amorphous carbon provides space for the volume expansion of the silicon particles, preventing the negative electrode material from pulverizing.
[0034] Specifically, the mass ratio of the carbon nanotubes, polymer, and solvent is 10-15:5-8:77-85. By controlling the mass ratio of these substances, the carbon layer of the prepared silicon-carbon composite material not only contains sufficient porosity to ensure that the silicon particles have sufficient volume expansion space, but also ensures the overall structural stability of the silicon-carbon composite material and good electrical conductivity. Specifically, in other embodiments, the mass ratio of the carbon nanotubes, polymer, and solvent is 12-13:6-7:80-82.
[0035] Specifically, the carbon nanotubes are at least one of multi-walled carbon nanotubes and single-walled carbon nanotubes.
[0036] The polymer is at least one of polyvinylpyrrolidone, polyacrylic acid polymers, polyether polymers, and polyurethane polymers. These polymers not only form porous amorphous carbon that cross-links with carbon nanotubes after carbonization, but also act as dispersants for carbon nanotubes, improving the dispersion effect of carbon nanotubes and enabling carbon nanotubes to be uniformly coated on the surface of silicon particles, which is beneficial to improving the structural stability and conductivity of silicon-carbon composite materials.
[0037] Specifically, the solvent is water or NMP.
[0038] The flow velocity of the carbon source solution in the reaction chamber is 10 m / s-20 m / s. Controlling the flow velocity of the solution, and consequently the surrounding air pressure, ensures a sufficiently low air pressure within the reaction chamber, allowing the air in the silicon powder to expand and disperse the silicon particles. Specifically, in the embodiments, the flow velocity of the carbon source solution in the reaction chamber can be, but is not limited to, 10 m / s, 11 m / s, 12 m / s, 13 m / s, 14 m / s, 15 m / s, 16 m / s, 17 m / s, 18 m / s, 19 m / s, or 20 m / s.
[0039] Specifically, the air pressure in the low-pressure zone is -0.01 MPa to -0.06 MPa. By controlling the air pressure in the low-pressure zone, the air in the silicon powder can expand in volume, thereby achieving the purpose of silicon particle dispersion.
[0040] In this embodiment, the gas pressure in the storage zone is greater than the gas pressure in the reaction chamber. When the gas pressure in the storage zone is greater than the gas pressure in the reaction chamber, as the mixed solution flows from the outlet of the reaction chamber into the storage zone, the liquid is forced into the spaces between the particles under pressure, further improving the dispersion effect of silicon particles in the carbon-containing solution. This results in smaller silicon particle sizes encapsulated in the silicon-carbon composite material, which is more conducive to solving the problem of large volume changes in silicon-carbon anode materials during charging and discharging. Specifically, in the embodiments, the gas pressure in the low-pressure zone can be, but is not limited to, -0.01 MPa, -0.02 MPa, -0.03 MPa, -0.04 MPa, -0.05 MPa, or -0.06 MPa.
[0041] Specifically, the gas pressure in the storage zone is not less than one atmosphere. By controlling the gas pressure in the storage zone, and because the gas pressure in the storage zone is relatively high, when the solution is discharged from the reaction chamber and enters the storage zone, the liquid is forced into the gaps between the silicon particles by the pressure, further dispersing the silicon particles. This is beneficial to improving the dispersion effect of silicon particles in the carbon source solution and solving the problem of large volume changes of silicon-carbon anode materials during charging and discharging.
[0042] The silicon powder is either nano-silicon or cracked silicon. Nano-silicon has a small particle size, which helps solve the problem of large volume changes in silicon-carbon anode materials during charging and discharging. Cracked silicon contains irregular cracks with air trapped within them. When cracked silicon enters a low-pressure region, the air in the cracks expands, causing the cracked silicon to break down into smaller, irregular silicon particles, which are then mixed with a carbon source solution. Cracked silicon has a larger particle size than nano-silicon and is significantly cheaper, thus reducing production costs. Furthermore, it eliminates the need for additional grinding or crushing of the silicon; the silicon itself breaks down during mixing with the carbon source solution to obtain smaller silicon particles, resulting in higher production efficiency.
[0043] The method for preparing cracked silicon is as follows: immerse untreated silicon in an alkaline solution with a mass percentage concentration of 1%-5%, react at 80-85℃ for 20-30 minutes, then wash with water until neutral and dry to obtain cracked silicon.
[0044] This invention uses an alkaline solution to hydrothermally corrode silicon to create cracks. By controlling the concentration of the alkaline solution, the reaction temperature, and the reaction time, it is beneficial to generate more irregular cracks on and inside the silicon surface, so that smaller silicon particles can be obtained after silicon is broken. Specifically, the silicon particles obtained after silicon is broken have a particle size of 1-100 μm.
[0045] The untreated silicon has a particle size of 1000-5000 μm. The alkaline solution is a strong potassium oxide solution or a sodium hydroxide solution.
[0046] Specifically, in the embodiments, the mass concentration of the alkaline solution can be, but is not limited to, 1%, 2%, 3%, 4%, or 5%; the reaction temperature between the alkaline solution and silicon can be, but is not limited to, 80°C, 81°C, 82°C, 83°C, 84°C, or 85°C; and the reaction time can be, but is not limited to, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min, or 30 min. The particle size of the untreated silicon can be, but is not limited to, 1000 μm, 2000 μm, 3000 μm, 4000 μm, or 5000 μm, and the particle size of the crushed silicon particles can also be 1-50 μm or 50-100 μm.
[0047] The present invention also provides a silicon-carbon composite material prepared by the above preparation method, which includes silicon particles and a carbon layer covering the outer surface of the silicon particles, wherein the carbon layer is formed by cross-linking carbon nanotubes and porous amorphous carbon.
[0048] Carbon nanotubes crosslink with porous amorphous carbon to form a carbon layer, meaning that carbon nanotubes are interspersed in the porous amorphous carbon layer, encapsulating silicon particles and forming a reinforced concrete-like structure on the surface of the silicon particles. This improves the overall structural stability of the silicon-carbon composite material. Furthermore, carbon nanotubes have excellent conductivity, which can enhance the conductivity of the silicon-carbon composite material. The porous amorphous carbon also provides space for the volume expansion of the silicon particles, preventing the negative electrode material from pulverizing.
[0049] To enable those skilled in the art to clearly understand the above-described implementation details and operations of the present invention, and to demonstrate the significant advancements in the performance of the embodiments of the present invention, the following examples illustrate the above technical solutions.
[0050] Example 1
[0051] A method for preparing a silicon-carbon composite material includes the following preparation steps:
[0052] S1. The carbon source solution is pumped into the reaction chamber, where it flows at a high speed of 10 m / s. A low-pressure zone with a pressure of -0.01 MPa is formed around the high-speed flowing carbon source solution. Nano-silicon powder is introduced into the low-pressure zone, where the air between the nano-silicon powder particles expands, causing the silicon particles in the nano-silicon powder to be dispersed. The nano-silicon powder is also drawn into the high-speed flowing carbon source solution. After mixing, the carbon source solution wets the silicon particles and coats their surface. Finally, the mixed solution is discharged into the storage zone, where the pressure is one atmosphere.
[0053] S2. The mixed solution in the storage area is dried at 50°C to obtain a mixture of silicon particles, carbon nanotubes and polymers, with the carbon nanotubes and polymers coating the surface of the silicon particles.
[0054] S3. Next, the mixture obtained from drying in S2 is subjected to carbonization treatment. Under a nitrogen atmosphere, the nitrogen flow rate is controlled at 2L / min, and the temperature is increased to 350℃ at a heating rate of 3℃ / min. The temperature is held for 2 hours, and then increased to 800℃ at a heating rate of 2℃ / min for 3 hours. After that, it is naturally cooled to room temperature, and the carbonized product is taken out.
[0055] S4. The product carbonized by S3 is pulverized and sieved to obtain a silicon-carbon composite material.
[0056] The mass ratio of the carbon source solution to the silicon powder is 9:1.
[0057] The carbon source solution comprises multi-walled carbon nanotubes, polyvinylpyrrolidone, and water, wherein the mass ratio of multi-walled carbon nanotubes, polyvinylpyrrolidone, and water is 10:5:85.
[0058] The silicon-carbon composite material prepared by the above method includes silicon particles and a carbon layer covering the outer surface of the silicon particles. The carbon layer is formed by the cross-linking of carbon nanotubes and porous amorphous carbon.
[0059] Example 2
[0060] A method for preparing a silicon-carbon composite material includes the following preparation steps:
[0061] S1. The carbon source solution is pumped into the reaction chamber. The carbon source solution flows at a high speed of 15 m / s in the reaction chamber. A low-pressure zone with a pressure of 0.03 MPa is formed around the high-speed flowing carbon source solution. The nano-silicon powder is introduced into the low-pressure zone. The air between the nano-silicon powder particles expands in the low-pressure zone, which disperses the silicon particles in the nano-silicon powder. The nano-silicon powder is also drawn into the high-speed flowing carbon source solution. After mixing, the carbon source solution wets the silicon particles and coats the surface of the silicon particles. Finally, the mixed solution is discharged into the storage zone, where the pressure is one atmosphere.
[0062] S2. The mixed solution in the storage area is dried at 50°C to obtain a mixture of silicon particles, carbon nanotubes and polymers, with the carbon nanotubes and polymers coating the surface of the silicon particles.
[0063] S3. Next, the mixture obtained from drying in S2 is subjected to carbonization treatment. Under a nitrogen atmosphere, the nitrogen flow rate is controlled at 2L / min, and the temperature is increased to 350℃ at a heating rate of 3℃ / min. The temperature is held for 2 hours, and then increased to 800℃ at a heating rate of 2℃ / min for 3 hours. After that, it is naturally cooled to room temperature, and the carbonized product is taken out.
[0064] S4. The product carbonized by S3 is pulverized and sieved to obtain a silicon-carbon composite material.
[0065] The mass ratio of the carbon source solution to the silicon powder is 9:1.
[0066] The carbon source solution comprises multi-walled carbon nanotubes, polyacrylic acid polymer, and water, wherein the mass ratio of the multi-walled carbon nanotubes, polyacrylic acid polymer, and water is 12:6:82.
[0067] The silicon-carbon composite material prepared by the above method includes silicon particles and a carbon layer that coats the outer surface of the silicon particles. The carbon layer is formed by the cross-linking of carbon nanotubes and porous amorphous carbon.
[0068] Example 3
[0069] A method for preparing a silicon-carbon composite material includes the following preparation steps:
[0070] S1. The carbon source solution is pumped into the reaction chamber. The carbon source solution flows at a high speed of 20 m / s in the reaction chamber. A low-pressure zone with a pressure of -0.06 MPa is formed around the high-speed flowing carbon source solution. The nano-silicon powder is introduced into the low-pressure zone. The air between the nano-silicon powder particles expands in the low-pressure zone, which disperses the silicon particles in the nano-silicon powder. The nano-silicon powder is also drawn into the high-speed flowing carbon source solution. After mixing, the carbon source solution wets the silicon particles and coats the surface of the silicon particles. Finally, the mixed solution is discharged into the storage zone, where the pressure is one atmosphere.
[0071] S2. The mixed solution in the storage area is dried at 50°C to obtain a mixture of silicon particles, carbon nanotubes and polymers, with the carbon nanotubes and polymers coating the surface of the silicon particles.
[0072] S3. Next, the mixture obtained from drying in S2 is subjected to carbonization treatment. Under a nitrogen atmosphere, the nitrogen flow rate is controlled at 2L / min, and the temperature is increased to 350℃ at a heating rate of 3℃ / min. The temperature is held for 2 hours, and then increased to 800℃ at a heating rate of 2℃ / min for 3 hours. After that, it is naturally cooled to room temperature, and the carbonized product is taken out.
[0073] S4. The product carbonized by S3 is pulverized and sieved to obtain a silicon-carbon composite material.
[0074] The mass ratio of the carbon source solution to the silicon powder is 9:1.
[0075] The carbon source solution comprises multi-walled carbon nanotubes, polyvinylpyrrolidone, and water. The mass ratio of the multi-walled carbon nanotubes, polyvinylpyrrolidone, and water is 15:8:77.
[0076] The silicon-carbon composite material prepared by the above method includes silicon particles and a carbon layer that coats the outer surface of the silicon particles. The carbon layer is formed by the cross-linking of carbon nanotubes and porous amorphous carbon.
[0077] Example 4
[0078] A method for preparing a silicon-carbon composite material. The difference between the preparation method of Example 4 and Example 3 is that the silicon powder in Example 4 is cracked silicon. The other steps are the same as those in Example 3, and will not be repeated here.
[0079] The method for preparing cracked silicon is as follows: Untreated silicon with a particle size of 3000 μm is immersed in a 3% potassium hydroxide alkaline solution and reacted at 82°C for 25 min. Then, it is washed with water until neutral and dried to obtain cracked silicon.
[0080] In the low-pressure zone, the air between the silicon powder particles and the air in the cracks of the silicon powder expands, causing the cracked silicon to break up and disperse. Specifically, the silicon particles obtained after the silicon is broken up have a particle size of 1-50μm.
[0081] Performance testing:
[0082] The silicon-carbon composite materials obtained in Examples 1-4 were used to prepare anode materials, and their performance was tested using 1C. The test results are as follows. The anode materials were prepared by mixing the silicon-carbon composite material with graphite, sodium polyacrylate, and sodium carboxymethyl cellulose in a mass ratio of 10:85:1:4.
[0083]
[0084] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A method for preparing a silicon-carbon composite material, characterized in that, The preparation steps include the following: Step 1: The carbon source solution is transported to the reaction chamber. The carbon source solution flows at high speed in the reaction chamber, and a low-pressure zone is formed around the high-speed flowing carbon source solution. Silicon powder is introduced into the low-pressure zone, and the air pressure in the low-pressure zone is -0.01MPa to -0.06MPa. The air between the silicon powder particles expands in the low-pressure zone, causing the silicon particles to be dispersed. The silicon powder is also drawn into the high-speed flowing carbon source solution and discharged into the storage zone. Step 2: The mixed solution in the storage area is dried, carbonized, pulverized, and sieved to obtain a silicon-carbon composite material.
2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that, The carbon source solution includes carbon nanotubes, polymers, and solvents.
3. The method for preparing silicon-carbon composite material according to claim 2, characterized in that, The mass ratio of the carbon nanotubes, polymer, and solvent is 10-15:5-8:77-85.
4. The method for preparing silicon-carbon composite material according to claim 2, characterized in that, The polymer is at least one of polyvinylpyrrolidone, polyacrylic acid polymers, polyether polymers, and polyurethane polymers.
5. The method for preparing silicon-carbon composite material according to claim 1, characterized in that, The flow velocity of the carbon source solution in the reaction chamber is 10 m / s-20 m / s.
6. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that, The gas pressure in the liquid storage area is not less than one atmosphere.
7. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that, The silicon powder is nano-silicon or cracked silicon.
8. The method for preparing the silicon-carbon composite material according to claim 7, characterized in that, The method for preparing cracked silicon is as follows: Untreated silicon is immersed in an alkaline solution with a mass percentage concentration of 1-5%, reacted at 80-85℃ for 20-30 minutes, then washed with water until neutral and dried to obtain cracked silicon.
Citation Information
Patent Citations
Method for preparing lithium ion battery silicon-carbon anode material by using carbon nanotube
CN109830668A
Preparation method of silicon-carbon composite material
CN112133915A
